Mechanical Properties Analysis of Composites (PLA, Chitosan and Calcium Prosphate) for bone implants - fikri, Muhammad Luqman Saiful; Zaenudin, Moh Zaenudin; Ujianto, Onny; mahfud, Imam (Universitas Muhammadiyah Metro, 2024)
This research explores the mechanical properties of composites made from Polylactic Acid (PLA), chitosan, and calcium phosphate, which have potential applications in bone tissue engineering due to their biocompatibility and biodegradability. This research aims to optimize the strength and durability of composites for biomedical use, with a focus on tensile strength, elongation and surface hardness. This research found that the addition of calcium phosphate increased the tensile strength and hardness of the PLA matrix to optimal concentrations, the highest tensile strength value of 80 MPa while chitosan increased elasticity and ductility. The hardness test results show an average value of 309 HV/100. The combination of these materials produces a balanced composite with better mechanical properties, making it suitable for bone implant applications.